Science Scholars: Integrating Scientific Research Into Undergraduate Medical Education Through a Comprehensive Student-Led Preclinical Elective - Marek Svoboda; Yasmin Kamal; Roshini Pinto-Powell (Association of American Medical Colleges, 2021)
Introduction One of the goals of evidence-based medical education is to familiarize future health care practitioners with the scientific method so they can interpret scholarly literature and communicate appropriately with patients. However, many students lack the skills necessary to conduct research themselves. We describe a preclinical elective course designed to equip students with these skills through workshops, mentorship, and research experience. Methods Through an application process, we selected first-year medical (M1) students who expressed interest in conducting basic, translational, or clinical research. Throughout the yearlong curriculum, students attended a series of 10 1-hour workshops to learn the skills necessary to engage in research. Additionally, each student was paired with a peer mentor. As their final project, students completed a specific aims page based on their projected research study. Results Over the course of 3 years, 96% of students secured a research position for the summer following M1, and 36% secured positions at external institutions with nationally competitive funding, compared to 10% of their peers who did not participate in the elective. Of students, 80% indicated that this elective helped them find and secure these research positions, and 75% of students reported that they learned valuable skills not taught in their medical curriculum. Discussion Participation in a preclinical research elective can provide immediate value in the form of research skills with the prospect of stimulating a lifelong interest in scientific inquiry. Our curriculum was delivered in a medical school setting, however it is applicable to any health care professional school.